Benchmarks for the interpretation of esophageal high‐resolution manometry. Issue 4 (13th October 2016) - Yadlapati, R.; Keswani, R. N.; Dunbar, K. B.; Gawron, A. J.; Gyawali, C. P.; Kahrilas, P. J.; Katz, P. O.; Katzka, D.; Spechler, S. J.; Tatum, R.; Pandolfino, J. E.
Abstract: Background: Competent interpretation of esophageal high‐resolution manometry (HRM) is integral to a quality study. Currently, methods to assess physician competency for the interpretation of esophageal HRM do not exist. The aim of this study was to use formal techniques to (i) develop an HRM interpretation exam, and (ii) establish minimum competence benchmarks for HRM interpretation skills at the trainee, physician interpreter, and master level. Methods: A total of 29 physicians from 8 academic centers participated in the study: 9 content experts separated into 2 study groups—expert test‐takers (n=7) and judges (n=2), and 20 HRM inexperienced trainees ("trainee test‐taker"; n=20). We designed the HRM interpretation exam based on expert consensus. Expert and trainee test‐takers (n=27) completed the exam. According to the modified Angoff method, the judges reviewed the test‐taker performance and established minimum competency cut scores for HRM interpretation skills. Key Results: The HRM interpretation exam consists of 22 HRM cases with 8 HRM interpretation skills per case: identification of pressure inversion point, hiatal hernia >3 cm, integrated relaxation pressure, distal contractile integral, distal latency, peristaltic integrity, pressurization pattern, and diagnosis. Based on the modified Angoff method, minimum cut scores for HRM interpretation skills at the trainee, physician interpreter, and master level ranged from 65–80%, 85–90% (with the exception of peristaltic integrity), and 90–95%, respectively. Conclusions & Inferences: Using a formal standard setting technique, we established minimum cut scores for eight HRM interpretation skills across interpreter levels. This examination and associated cut scores can be applied in clinical practice to judge competency. Abstract : Currently, there is a gap in competency‐based training and assessment for esophageal high‐resolution manometry (HRM). Using formal standard setting techniques among a group of esophageal experts, we created an exam for the interpretation of esophageal HRM. In addition, we established minimum competency cut scores for esophageal HRM skills at the trainee, physician interpreter, and master level.